2016
DOI: 10.1007/s10654-016-0152-8
|View full text |Cite
|
Sign up to set email alerts
|

Are some populations resilient to recessions? Economic fluctuations and mortality during a period of economic decline and recovery in Finland

Abstract: This paper uses individual-level longitudinal data on working-age Finns to examine the health effects of economic fluctuations during a period of economic decline (1989–1996) and recovery (1997–2007) in Finland. We used a nationally representative, longitudinal sample formed by linking population, employment and mortality registers (n = 698,484; 7,719,870 person-years). We implemented a region fixed-effect model that exploits within-regional variations over time in the unemployment rate to identify the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
0
14
2
Order By: Relevance
“…men and women living without a partner and tenants of dwellings. On the other hand, while some suggest that unemployment has a more detrimental health effect for high-educated men, because of their higher career expectations and the potentially larger losses [8], we observed a reversed gradient. Among the unemployed, low-educated men had higher mortality risks compared with high-educated men, whereas for women, mortality was equally across educational attainment.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…men and women living without a partner and tenants of dwellings. On the other hand, while some suggest that unemployment has a more detrimental health effect for high-educated men, because of their higher career expectations and the potentially larger losses [8], we observed a reversed gradient. Among the unemployed, low-educated men had higher mortality risks compared with high-educated men, whereas for women, mortality was equally across educational attainment.…”
Section: Discussioncontrasting
confidence: 73%
“…Indeed, many studies have suggested that being unemployed can be harmful in several ways, not only financially and psychosocially, but also healthwise [1,7,1017]. Unemployment has shown to be associated with both mental and physical ill-health and mortality [7,8,1012,1519,2022]. Yet, there might be a protective effect of contextual economic recession in which mortality rates tend to fall [8,15,16,21,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any mortality-increasing effects of the crisis were probably also buffered by the extensive social security and financially accessible health care systems still in place in most European countries (9). The latter interpretation finds support in detailed analyses of the lack of impact of previous recessions on health inequalities in the Nordic countries (19).…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies in Japan and Finland have shown the vulnerability of men with higher SES against the backdrop of recent economic recessions. 19 , 20 Their vulnerability could be exacerbated by a lack of marital protection. Furthermore, Japanese women with higher education are more likely to be single throughout their life, 21 which could elevate their risk for mortality.…”
Section: Introductionmentioning
confidence: 99%